2017
DOI: 10.1016/j.athoracsur.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers May Prognosticate Recurrence in Node-Negative, Non-Small Cell Lung Cancers Less Than 4 Centimeters

Abstract: Serum-based biomarkers may be useful for risk stratifying patients with node-negative NSCLC less than 4 cm for recurrence after lung resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The majority of the biomarker discovery research conducted in recent years has been devoted to the analysis of biomarkers isolated from serum or plasma, thanks to the fact that blood sampling can be carried out following a highly standardized method, reproducible, easy to perform worldwide, which is also applicable to the longitudinal analysis of samples, for tumor recurrence monitoring. [90] However, plasma proteomics represents a formidable task, due to the high complexity and extreme dynamic range of the proteins present in plasma (up to 10 11 ). In addition, a few proteins at very high concentrations are present (primarily albumin, which alone represents more than half of the total protein content of plasma), which mask low abundance proteins that may be differentially regulated and potentially disease-relevant.…”
Section: Biological Sample Typementioning
confidence: 99%
“…The majority of the biomarker discovery research conducted in recent years has been devoted to the analysis of biomarkers isolated from serum or plasma, thanks to the fact that blood sampling can be carried out following a highly standardized method, reproducible, easy to perform worldwide, which is also applicable to the longitudinal analysis of samples, for tumor recurrence monitoring. [90] However, plasma proteomics represents a formidable task, due to the high complexity and extreme dynamic range of the proteins present in plasma (up to 10 11 ). In addition, a few proteins at very high concentrations are present (primarily albumin, which alone represents more than half of the total protein content of plasma), which mask low abundance proteins that may be differentially regulated and potentially disease-relevant.…”
Section: Biological Sample Typementioning
confidence: 99%
“…The associations of PRL and development of various cancer has been evaluated in breast, prostate, colorectal, gynecological, and hepatocellular cancer ( Goffin, 2017 ). Only a few studies have examined the relationship between the PRL levels and lung cancer ( Caponnetto et al, 2017 ; Seder et al, 2017 ). PRL was introduced in a seven-analyte panel of lung cancer biomarkers for the first time and the panel was suggested useful to risk stratify cancer patients for early recurrence after resection of node-negative NSCLC less than 4 cm ( Seder et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Seder et al. reported that both b-HCG and prolactin might be useful serum biomarkers for identifying patients with higher probability of NSCLC recurrence after initial excision [7]. We present a rare case of a male patient with lung cancer, appearing with gynecomastia causing mastodynia and galactorrhea as initial symptoms.…”
Section: Introductionmentioning
confidence: 93%